Cyclamen Mite, Phytonemus pallidus (Banks) (Arachnida: Acarina: Tarsonemidae): EENY-178/IN335, rev. 8/2004 - Denmark, Harold A. (EDIS, 2021)
Revised! This document is EENY-178 (originally published as DPI Entomology Circulars 25, 177 and 306), part of the Featured Creatures collection. Published by the the Entomology and Nematology Department, UF/IFAS Extension, August 2004. EENY-178/IN335: Cyclamen Mite, Phytonemus pallidus (Banks) (Arachnida: Acari: Tarsonemidae) (ufl.edu)